X‐ray scatter correction for dedicated cone beam breast CT using a forward‐projection model. Issue 6 (25th April 2017) - Shi, Linxi; Vedantham, Srinivasan; Karellas, Andrew; Zhu, Lei
Abstract : Purpose: The quality of dedicated cone‐beam breast CT (CBBCT) imaging is fundamentally limited by x‐ray scatter contamination due to the large irradiation volume. In this paper, we propose a scatter correction method for CBBCT using a novel forward‐projection model with high correction efficacy and reliability. Method: We first coarsely segment the uncorrected, first‐pass, reconstructed CBBCT images into binary‐object maps and assign the segmented fibroglandular and adipose tissue with the correct attenuation coefficients based on the mean x‐ray energy. The modified CBBCT are treated as the prior images toward scatter correction. Primary signals are first estimated via forward projection on the modified CBBCT. To avoid errors caused by inaccurate segmentation, only sparse samples of estimated primary are selected for scatter estimation. A Fourier‐Transform based algorithm, herein referred to as local filtration hereafter, is developed to efficiently estimate the global scatter distribution on the detector. The scatter‐corrected images are obtained by removing the estimated scatter distribution from measured projection data. Results: We evaluate the method performance on six patients with different breast sizes and shapes representing the general population. The results show that the proposed method effectively reduces the image spatial non‐uniformity from 8.27 to 1.91% for coronal views and from 6.50 to 3.00% for sagittal views. The contrast‐to‐deviation ratio is improved by an average factor of 1.41. Comparisons on the image details reveal that the proposed scatter correction successfully preserves fine structures of fibroglandular tissues that are lost in the segmentation process. Conclusion: We propose a highly practical and efficient scatter correction algorithm for CBBCT via a forward‐projection model. The method is attractive in clinical CBBCT imaging as it is readily implementable on a clinical system without modifications in current imaging protocols or system hardware.